A study of the patis industry in Manila and its environs - Tesoro, Luz C. ([Quezon City], 1959)
The purpose of the study is to provide general information about the patis industry and to make observations on the latest trends in the manufacture of the sauce. A study of the patis industry will enable the visualization of the recent trends and problems of the industry. This study will be of help to any individual who desires to put up a plant of his own. Vital information about the industry will be included in this study.
No Abstract
Bibliography: l. 36.
Thesis (B.S. Food Tech.)--University of the Philippines.
Keywords: Patis industry